Will an Implementation of “Joy of Life in Nursing Homes” Have Positive Effect for the Work Culture? A Comparison Between Two Norwegian Municipalities - André, Beate; Heldal, Frode; Sjøvold, Endre; Haugan, Gørill (Frontiers in Psychology, 2021)
Background: When facing a social development where there are more elderly people and how many of them will need care in nursing homes, it is important to focus on the working culture of those who work there. Job satisfaction for nurses is influenced by both organizational factors and aspects of patient care. Norwegian municipalities have applied the Joy of Life Nursing Home (JoLNH) strategy representing a resource-oriented health-promoting approach. Knowledge about how implementation of the JoLNH approach impacts the work culture is scarce. Aims: To investigate if an implementation of the JoLNH strategy leads to positive impact for the work culture? Investigating the differences in the work culture between nursing homes who have implemented the JoLNH strategy and those who have not implemented this strategy. Method: Healthcare personnel in two large municipalities in Norway responded on a survey twice (T1 and T2). The data for the present study were collected in two waves, with a 1‐year interval, among employees from 43 nursing homes. The survey was completed by 558 employees at T1 and 515 at T2. Work culture was assessed by the Systematizing Person-Group Relations Instrument (SPGR). Findings: The municipality where the strategy was implemented experienced significant increases in C2 (Task-orientation), D1 (Conformity) and S2 (Empathic interest). These dimensions indicate a positive orientation towards both task and work culture. There is an increase in the W1 among those working in the non-JoLNH municipality; W1 along with W2 indicate non-talkative, not participating, non-responsive, passive, and low confidence behaviors (W1) as well as sad, complaining, expressing sorrow, disbelief, and self-pitying behaviors (W2). Discussion: The data clearly suggest that the implemented JoLNH strategy has endorsed positive effects in the work culture. The JoLNH strategy emphasizes quality of patient care, which healthcare personnel in general are much concerned about. Furthermore, attention on task orientation and independent work may encourage a better work culture. Conclusion: The present findings imply that implementation of the JoLNH strategy highlighting care quality and task orientation facilitates a positive work culture in nursing homes.